Penggunaan Model Pembelajaran Science Environment Technology and Society (Sets) untuk Meningkatkan Kemampuan Berpikir Kritis dan Sikap Ilmiah - Maimunah Maimunah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2016)
This study aimed to determine the improvement of critical thinking skills and student’s scientific attitudes on the colloidal material by applying the learning model science environment technology and society (SETS). The method was used in this study is quasi-experimental research design